Who is the Expert? Integrated Urban Modeling and the Reconfiguration of Expertise. Issue 2 (3rd April 2017) - Commenges, Hadrien; Tomasoni, Lorenza; Seigneur, Christian; Bonin, Olivier; Leurent, Fabien; Bonhomme, Céline; Deroubaix, José-Frédéric
ABSTRACT: Much has been spoken and written about the rationalization and optimization of services and amenities in urban territories. In this context, there is increasing use of numerical modeling techniques addressing the design, selection and/or calibration of policy instruments. The question of the relations between appraisal tools and policymaking has been widely studied. However, few studies have specifically focused on the role of modeling in policymaking processes. Drawing on two case studies, this paper suggests a change in the nature of multi-expertise: neither conflicting nor cross-sectoral, we observed in both cases an interwoven configuration with a network of experts making use of integrated models. We call this configuration distributed expertise, arguing that it is a novel configuration and that its emergence is closely linked to the development of integrated modeling techniques. Other authors have discussed the idea that the growing need for new appraisal tools is linked with the proliferation of wicked policy problems. From our case studies we would conclude that the emergence of integrated modeling is not a response to complex problems but to complex systems of actors who need to reach a consensus on actions.